Incidence of Infectious Morbidity Events after Second-Line Antiretroviral Therapy Initiation in HIV-Infected Adults in Yaoundé, Cameroon. Issue 6 (August 2016) - ,; Galy, Adrien; Ciaff, Laura; Le Moing, Vincent; Eymard-Duvernay, Sabrina; Abessolo, Hermine; Toby, Roselyne; Ayangma, Liliane; Le Gac, Sylvie; Mpoudi-Etame, Mireille; Koulla-Shiro, Sinata; Delaporte, Eric; et al.
Background: Since antiretroviral therapy (ART), HIV-infected individuals experience mainly non-AIDS-related conditions, among which infectious events are prominent. We aimed to estimate incidence and describe overall spectrum of infectious events, including all grade events, among HIV-1-infected adults failing first-line ART in Yaoundé, Cameroon. Methods: All patients from Cameroon enrolled in the second-line ART 2LADY trial (ANRS12169) were included in this secondary analysis. Medical files were reviewed with predefined criteria for diagnosis assessment. Incidence rates (IR) were estimated per 100 person-years (% PY). Results: A total of 302 adult patients contributing 840 PY experienced 596 infectious events (IR 71% PY). Only 29 (5%) events were graded as severe. Most frequent infections were upper respiratory tract infections (15% PY), diarrhoea (9% PY) and malaria (9% PY). A total of 369 (62%) infections occurred during the first year (IR 130% PY) followed by a persistent lower incidence during the following 3 years. Higher IR were observed in patients with CD4 + T-cell count ≤200 cells/mm 3 for all infectious events except for mycobacterial and parasitic infections. IR of viral, bacterial and parasitic infectious events were lower in case of co-trimoxazole use in patients with CD4 + T-cell count ≤200 cells/mm 3 . Conclusions: Infectious events are common and mainly occur during the first year after treatment initiation. Second-line ART initiation had a positive impact on the entire spectrum of infectious morbidity.